Quality assurance of vital® test meal in gastric emptying scintigraphy - Wen, Ngo Hui (Universiti Sains Malaysia, 2024)
In vivo studies of gastric emptying scintigraphy (GES) had demonstrated that the high-calorie drink, Vital® could serve as an alternative to people who cannot tolerate the conventional solid egg-white meal (EWM). Further evaluations were needed to ensure its reliability as a liquid meal for GES. Therefore, we sought to address two quality assurance aspects to validate Vital®, which included uniform dispersion of the radiotracer and in vitro radiolabelling efficiency and stability. Methods: A simple mixing method was proposed where 99mTc-phytate (99mTc-P) was injected into the Vital® drink without removing the aluminium seal, and it was gently swirled for a minute. The drink was then imaged for 15 minutes using dynamic scintigraphy and an analysis of the regions of interest (ROI) at the top and bottom of the of the drink was done. For the radiolabelling efficiency and stability experiment, 12 samples of Vital® were mixed with 99mTc-P, incubated with human saliva supernatant and gastric fluid for 4 hours, then centrifuged and filtered at hourly intervals. The radioactivity of the solid part and filtrate was assessed using 1-minute static imaging. Findings: Results showed no significant differences in activity percentages between the top and bottom of the drink over 15 minutes (p >0.05), suggesting a uniform distribution of the radiotracer throughout the drink. Significantly more radioactivity was found in the filtrate compared to the solid part (p <0.05), indicating a preferential radiolabelling of the aqueous phase of Vital®. The radiotracer remained stable in both the solid and aqueous phases of Vital® in the simulated gastric environment over 2-4 hours, with no significant differences observed between each time point (p >0.05). Conclusions: This study offered detailed insights into how the high- calorie Vital® nutrient drink behaves, improving the understanding of previous GES findings. It could serve as a key reference for future research and clinical practices in choosing and preparing liquid test meals, leading to more accurate GES results.